Gender transition shapes perceived sexual orientation. Issue 4 (19th May 2021) - Spielmann, Julia; Stern, Chadly
ABSTRACT: We examined whether and why the amount of time a transgender person has spent transitioning influences perceived sexual orientation. We found that transgender individuals who had spent more time transitioning were more likely to be categorized as straight (vs. gay), and that greater gender typicality in part accounted for shifts in perceived sexual orientation. These perceptions were not contingent on whether people made judgments about how they personally felt or what the average person would say. Overall, these findings support the idea that gender and sexuality intersect in people's minds, and that shifts in one can lead to changes in perceptions of the other. We discuss how these findings contribute to understanding perceptions and experiences of transgender individuals.